فعالية استخدام الذكاء الاصطناعي في العملية البحثيةمن وجهة نظر الوزارة الوصية - دراسة ميدانية على عينة من طلبة الماستر بكلية العلوم الإنسانية والاجتماعية بجامعة محمد بوضياف - المسيلة- - نويوةمنـــال (جامعــــــــــــــة محمــــــــد بوضيـــــــــاف – المسيلـــــــــــــة, 2025)
هدفت هذه الدراسة إلى تحديد درجة فعالية إستخدام الذكاء في تحسين جودة العملية البحثية، من خلال قرار وزارة التعليم العالي والبحث العلمي بدمج الذكاء الإصطناعي ضمن المنظومة التعليمية،وإصدار قرار إلزامي يتدريس مقياس الذكاء الإصطناعي في مختلف المستويات والتخصصاتالجامعية، إبتداء بطلبة السنة أولى ماستر لسنة الجامعية2024/2025،وهذا ما حولنا هذه الدراسة الإجابة على التساؤل الرئيسي:"ما فعالية إستخدام الذكاء الإصطناعي في العملية البحثية وفق رؤية وزارة التعليم العالي والبحث العلمي؟ " إعتمدنا في دراستنا على المنهج الوصفي التحليلي،مع توظيف نظريةإنتشار المبتكرات، كما تم الإستعانةبإستمارةإستبيان في عملية جمع البيانات،التي تم توزيعها على عينة قدرها 100مفردة، من طلبة سنة أولى ماستر من كلية العلوم الإنسانية والإجتماعية بمختلف تخصصاتها، أظهرت نتائج الدراسة بأن للذكاء الإصطناعي فعالية كبيرة في تحسين جودة العملية البحثية، كما كشفت نتائج الدراسة على وجود علاقة بين الذكاء الإصطناعيوالبحثالعلمي، كما حددت أهم إنعكاسات و مخاطر إستخدام الذكاء الإصطناعيفي البحث العلمي. Our studyaimed to determine the degree of effectiveness of using intelligence in improving the quality of scientificresearch, through the decision of the Ministry of Higher Education and Scientific Research to integrate intelligence into the educational system, and issuing a mandatorydecision to teach the artificial intelligence standard at variousuniversitylevels and specializationsstartingwith first-yearMaster’sstudents for the academicyear 2024/2025, and thisiswhatweasked in ourstudy to answer the main question: "Whatis the effectiveness of usingartificial intelligence in scientificresearchaccording to the vision of the Ministry of Higher Education and Scientific Research ?" . In our study, we relied on the descriptive analytical method, as well as on the theory of the diffusion of innovations.A questionnaire form was also used in the data collection process, which was distributed to a sample of 100 individuals, first-year master’s students from the Faculty of Humanities and Social Sciences in its various specializations. The results of the study showed that artificial intelligence has great effectiveness in improving the quality of the research process.The results of the study also revealed the existence of a relationship between artificial intelligence and scientific research, and also identified the most important implications and risks of using artificial intelligence in scientific research.